Pertanggungjawaban Hukum Terhadap Anak Yang Melakukan Tindak Pidana Pembunuhan : (Studi Kasus Putusan No. 3/PID.Sus-Anak/2022/PN BNT) - Difqa Alvi Ramadhandiko; Rara Siti Sandiah; Anissa Nabilla; Nabila Putri Adelita; Handoyo Prasetyo (Lembaga Pengembangan Kinerja Dosen, 2024)
The phenomenon of children dealing with the law with their position as perpetrators is increasingly troubling the community, especially children who are perpetrators of murder. In this case there are two conflicting legal norms related to children's responsibility and children's rights in obtaining legal protection. The purpose of this study is to determine the form of child responsibility in terms of the Juvenile Justice System Law and to find out the solution in handling cases of children who become perpetrators of criminal acts without overriding their rights based on the case in decision No. 3/Pid.Sus-Anak/2022/PN Bnt. The method used is a normative juridical approach. The research was conducted by utilizing secondary data in the form of court decisions and other literature studies. The results showed that based on the Juvenile Justice System Law, the judicial process involves various competent parties and focuses on education and rehabilitation, with lighter sanctions and educational in nature. In the case of the Decision, the child was sentenced to 9 years and 6 months imprisonment in LPKA. In addition, not only punishment, but children are also given the necessary guidance and education as a form of fulfillment of their rights in order to improve their behavior.